Predictors of family focused practice: organisation, profession, or the role as child responsible personnel? - Bjørg Eva Skogøy; Terje Ogden; Bente Weimand; Torleif Ruud; Knut Sørgaard; Darryl Maybery (BMC, 2019)
Abstract Background Health professionals in Norway are required by law to help safeguard information and follow-up with children of parents with mental or physical illness, or who have substance abuse problems, to reduce their higher risk of psychosocial problems. Knowledge is lacking regarding whether organisation and/or worker-related factors can explain the differences in health professionals' ability to support the families when patients are parents. Methods Employing a translated, generic version of the Family Focused Mental Health Practice Questionnaire (FFPQ), this cross-sectional study examines family focused practice (FFP) differences in relation to health professionals' background and role (N = 280) along with exploring predictors of parent, child, and family support. Results While most health professions had begun to have conversations with parents on children's needs, under one-third have had conversations with children. There were significant differences between nurses, social workers, psychologists, physicians, and others on seven of the FFP subscales, with physicians scoring lowest on five subscales and psychologists providing the least family support. Controlling for confounders, there were significant differences between child responsible personnel (CRP) and other clinicians (C), with CRP scoring significantly higher on knowledge and skills, confidence, and referrals. Predictors of FFP varied between less complex practices (talking with parents) and more complex practices (family support and referrals). Conclusion The type of profession was a key predictor of delivering family support, suggesting that social workers have more undergraduate training to support families, followed by nurses; alternately, the results could suggest that that social workers and nurses have been more willing or able than physicians and psychologists to follow the new legal requirements. The findings highlight the importance of multidisciplinary teams and of tailoring training strategies to health professionals' needs in order to strengthen their ability to better support children and families when a parent is ill.